2017
DOI: 10.1016/j.polymer.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

High service temperature, self-mendable thermosets networked by isocyanurate rings

Abstract: A new mending chemistry exhibiting stability at extreme temperatures and holding mechanical properties as well as mechanical stability comparable to widely used engineering plastics is reported here. This mendable thermoset polymer is synthesized using commodity reactants through the formation of a isocyanurate-oxazolidone network which exhibit a high service temperature as shown by their T g of 270°C and T d of 365°C. We demonstrate that this network polymer is repeatedly self-mendable in the presence of a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The chemical composition of the product under different reaction temperatures was investigated. As shown in Figure 2, the FTIR spectrum of the product after an 80 °C reaction shows the formation of isocyanurate (absorption band corresponding to the stretching CO vibration at 1710 cm −1 ) at this temperature, while no oxazolidone was detected (absorption band corresponding to the stretching CO vibration at 1750 cm −1 ) . When the reaction temperature was further increased to 150 °C, oxazolidone formed while the isocyanurate disappeared, as shown by the FTIR spectrum, indicating the isocyanurate‐to‐oxazolidone transformation at this elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemical composition of the product under different reaction temperatures was investigated. As shown in Figure 2, the FTIR spectrum of the product after an 80 °C reaction shows the formation of isocyanurate (absorption band corresponding to the stretching CO vibration at 1710 cm −1 ) at this temperature, while no oxazolidone was detected (absorption band corresponding to the stretching CO vibration at 1750 cm −1 ) . When the reaction temperature was further increased to 150 °C, oxazolidone formed while the isocyanurate disappeared, as shown by the FTIR spectrum, indicating the isocyanurate‐to‐oxazolidone transformation at this elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…For bulk polymerization of the ISOX polymers with nucleophiles such as tertiary amines, previous studies have shown agreement on the main reactions proceeding in the order of increased temperatures during the polymerization: (1) trimerization of isocyanate to isocyanurate, (2) oxazolidone formation from isocyanate and epoxide reaction, and (3) transformation of isocyanurate to oxazolidone through reaction with excessive epoxide . The isocyanurate and oxazolidone rings lead to a dense polymer network with a reported small molecular weight between crosslinks of 79 g/mol …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of reversibility, the majority of healing substances are classified as thermoplastic. A mendable thermoset polymer with a glass transition temperature (T g ) of 270 • C and decomposition temperature (T d ) of 365 • C was synthesized by Zhang et al [28]. The isocyanurate-oxazolidone polymer incorporated with mechano-responsive isocyanurate rings recovers its broken bonding by means of thermal annealing.…”
Section: New Materials and Approachesmentioning
confidence: 99%